Carbon Dots Enable Efficient Delivery of Functional DNA in Plants - Wang, Bo; Huang, Jian; Zhang, Mengling; Wang, Yun; Wang, Huibo; Ma, Yurong; Zhao, Xiaodong; Wang, Xiao; Liu, Changhong; Huang, Hui; Liu, Yang; Lu, Fang; et al. (ACS applied bio materials, 2020)
Genetic engineering is an important technology in plant sciences. The current delivery techniques, such as Agrobacterium-mediated gene transfer and gene gun instant gene expression system, always need a very complicated process or have host-range limitations due to the inhibition of the cell wall structure. Here, we demonstrate that a nanocomposite (CDP) prepared by combining polyethyleneimine (PEI) with carbon dot (CD) was confirmed as a good vector for gene transfection in both animal and plant cells, especially in intact plants. Efficient DNA delivery and strong gene expression without DNA integration are accomplished in rice (Oryza Sativa japonica), wheat (Triticum aestivum), and mung bean (Phaseolus radiatus) leaves and rice roots. Notably, the CDP successfully deliver the hydamycin resistance gene into the rice and induce hygromycin resistance in rice. Also, CDP can achieve the β-glucuronidase gene delivery and expression in mature rice embryo induced callus. The CDP not only facilitates plasmid transport into cells but also protects DNA from DNase degradation. Our work provides a highly efficient DNA delivery system for instant gene expression, which could be a useful and fast gene engineering tool for functional research in plant biology.